Cardiac Syncope with Anoxic Seizure Activity. (8th January 2020) - Talibi, Samed; Douglas, Craig; Pope, Benjamin
Abstract : This is a case report, which explores the presentation to the emergency department of a fit and well female with a known ventricular bigeminy. She presented with convulsive episodes. The working differential diagnosis was of possible cardiac syncope with anoxic seizure activity or neurogenically mediated arrhythmia secondary to subarachnoid haemorrhage. On further collateral history, the patient was on citalopram. The ECGs demonstrated PVCs of multiple morphologies that were transiently bidirectional, raising the possibility of catecholaminergic polymorphic ventricular tachycardia. The presentation of a young fit patient with syncope and seizure-like episodes should always raise concern for the admitting emergency medicine clinician of an underlying cardiac pathology.